Co 15002: A potential fifth generation inbred derivative developed through inbreeding followed by hybridization and selection for sugarcane improvement - Durai, A Anna; Hemaprabha, G; Mohanraj, K; Ram, Bakshi (Journal of Sugarcane Research, 2021)
Among 129 clones evaluated along with standard varieties CoC 671 and Co 86032 in Pre-zonal varietal trial (PZVT) during 2014-15, the clone PZVT 13-175 recorded the highest cane yield of 143.52 t/ha which was significantly superior to both the standards. Consequently the clone was given Co status i.e. Co 15002 and was included in Initial Varietal Trial of All India Co-ordinated research Project on Sugarcane in Peninsular Zone along with 25 other test entries and four standards at 15 test locations during the year 2018-19. Co 15002 registered significantly higher sucrose content (19.43%) than the commercially released sugarcane variety CoSnk 05103 (18.96 %) and on par with the ruling variety Co 86032 (19.63 %) at 10th month crop maturity. Cane yield of Co 15002 (96.27 t/ha) was found to be on par with the recently released CoSnk 05103 (97.23 t/ha) and CoC 671 (99.30 t/ha). Co 15002 was screened for red rot, smut and yellow leaf diseases under natural and artificially inoculated conditions at Coimbatore, Pune, Kolhapur and Navsari. Under natural conditions, smut and yellow leaf diseases were not observed. Co 15002 was resistant or moderately resistant to red rot by both plug and nodal methods in all the test locations. In artificial inoculated conditions, Co 15002 showed resistance to moderately resistant reaction to smut. It recorded 20 % flowering intensity and low pollen fertility of 30 % with peak flowering during the first fortnight of November and can be used as a pistil parent in hybridization programmes.